Penguatan Ketahanan Pangan dan Pencegahan Stunting melalui Bank Sayur di Desa Korowelangkulon Kendal - Wahyuningsih, Wahyuningsih; Jitni Patoni (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Korowelangkulon Village, Cepiring Sub-district, Kendal Regency, is one of the villages with stunting cases. Education about stunting, food security, and utilization of vacant land around the house are part of the efforts to deal with stunting within the family. The community service program carried out by the KKN-T 33 team of Alma Ata University Yogyakarta aims to improve food independence, family nutritional welfare, and farming skills. This activity uses the Asset-Based Community Development (ABCD) approach which consists of five stages: discovery (finding assets), dream (formulating dreams), design (designing strategies), define (determining actions), and destiny (program implementation). The main target of this program is the PKK cadres of Korowelangkulon Village. The results achieved include an increased understanding of PKK cadres about food security and stunting prevention through vegetable banks, the role of cadres as examples for the community, and increased skills in processing plastic waste as planting media. The vegetable bank program is expected to have a positive impact in increasing food self-sufficiency and preventing stunting in the family, while optimizing the local potential of the community.